Determinan Kehamilan Remaja: Analisis Pengetahuan, Peran Orang Tua, dan Pengaruh Teman Sebaya di Puskesmas Ciseeng - Rochmawati Rochmawati; Winnie Tunggal Mutika; Sri Hayuningsih; Ina Sugiharti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Indonesia's adolescent pregnancy prevalence necessitates comprehensive determinant identification for evidence-based preventive strategy formulation. This research analyzes correlations between reproductive health knowledge, parental role functioning, and peer influence on teenage pregnancy among female adolescents in Ciseeng Health Center, Bogor Regency, West Java Province. Cross-sectional design employed among 65 adolescents aged 15-19 years during October 2024-January 2025 using stratified random sampling. Data collection utilized validated questionnaires based on WHO Adolescent Sexual and Reproductive Health Indicators, Parental Monitoring and Support Scale, and Peer Pressure Inventory with Cronbach Alpha (α=0.84; 0.81; 0.79). Demographic characteristics showed 60% aged 17-19 years, 40% aged 15-16 years, with 55.4% experienced pregnancy validated through medical records. Univariate analysis identified knowledge deficiency (64.6%), parental dysfunction (63.1%), and high peer influence (66.2%). Chi-Square analysis confirmed associations of low knowledge (p=0.001; OR=3.5; 95% CI=1.8-6.7), inadequate parental roles (p=0.002; OR=3.2; 95% CI=1.6-6.1), and dominant peer influence (p=0.001; OR=3.8; 95% CI=1.9-7.2) with adolescent pregnancy. Multivariate logistic regression identified peer influence as strongest predictor (AOR=3.80; 95% CI=1.67-8.65).